Indonesian Economy Leading to a Political Year and How Foreign Banks Can Play a Role in Development - Kemal Aziz Stamboel (JAS (Journal of ASEAN Studies), 2014)
Recently, Indonesia’s economy records very high and stable economic growth. The growth is above 6 percent. Despite the world economic crisis, our economic growth is adequately resistant to turmoil from external crisis. The relatively high economic growth is mainly caused by high domestic demand, both from consumption and investment. The question is how foreign banks can play a role in development of Indonesian economy? In this notes, I discuss several challenges posed by structural changes in Indonesia as well as opportunities for foreign banks to play a role in Indonesian financial development.